INVESTIGATING CHALLENGES EXPERIENCED BY INTERMEDIATE PHASE MATHEMATICS TEACHERS IN THE IMPLEMENTATION OF FORMATIVE ASSESSMENTS - Sibanda, Senzeni; Rambuda, Awelani Melvin (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas PGRI Mahadewa Indonesia, 2024)
In this empirical paper, the authors discuss the challenges experienced by the intermediate phase teachers in the implementation of formative assessments in mathematics teaching and learning. Numerous reports regarding South African learners' poor performance in mathematics necessitated the research. Challenges associated with the language of learning and teaching are the primary contributors of this issue. The paper is grounded in the social constructivist theory which places emphasis on the notion that learning occurs when learners are provided with opportunities to apply the cultural psychological mechanisms they utilize, that include mathematical concepts, language, and diagrams and then taught the way to apply those mechanisms as to gain an in-depth comprehension of (some) phenomenon. In this quantitative paper, the questionnaire was administered to 151 respondents to elicit information on assessment challenges. The study found that the implementation of formative assessments poses a challenge to most of the in-service teachers. Considering these findings, the study recommends that subject advisors and policy makers provide ongoing professional development for teachers regarding the implementation of formative assessments. Additionally, teachers should employ the social constructivist approach while assessing learners, particularly for projects and investigations as forms of formative assessments.